Configurações de ciclos de vida na literatura para crianças: uma análise ecolinguística - Ramos, Rui (2017)
This study analysis a group of picturebooks aimed at children. These picture books have the potential to promote the young readers’ ecoliteracy, and they all deal with the theme of life cycle. In these books, the aesthetic, the playful and the ethical / educational aspects of children’s literature articulate with each other harmoniously. They are socially relevant manifestations of an ecological discourse that is present in contemporary western societies. The selected theoretical framework is that of discourse studies, and the research attributes special attention to the construction of the speech objects.